2023
DOI: 10.1002/jcsm.13284
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term disuse does not affect postabsorptive or postprandial muscle protein fractional breakdown rates

Abstract: BackgroundThe decline in postabsorptive and postprandial muscle protein fractional synthesis rates (FSR) does not quantitatively account for muscle atrophy during uncomplicated, short‐term disuse, when atrophy rates are the highest. We sought to determine whether 2 days of unilateral knee immobilization affects mixed muscle protein fractional breakdown rates (FBR) during postabsorptive and simulated postprandial conditions.MethodsTwenty‐three healthy, male participants (age: 22 ± 1 year; height: 179 ± 1 cm; bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…We next investigated the impact of NR4A3 downregulation on markers of protein degradation. Although the contribution of protein breakdown towards disuse muscle atrophy is unclear in humans [2, 12], the ubiquitin-proteasomal (UPS) and autophagy-lysosomal systems are markedly induced during rodent models of inactivity [18, 19]. Additionally, skeletal muscle-specific NR4A3 transgenic mice display greater autophagic flux [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next investigated the impact of NR4A3 downregulation on markers of protein degradation. Although the contribution of protein breakdown towards disuse muscle atrophy is unclear in humans [2, 12], the ubiquitin-proteasomal (UPS) and autophagy-lysosomal systems are markedly induced during rodent models of inactivity [18, 19]. Additionally, skeletal muscle-specific NR4A3 transgenic mice display greater autophagic flux [42].…”
Section: Resultsmentioning
confidence: 99%
“…Detriments in both mTORC1 [9] and ribosomal abundance [10] are observed in human skeletal muscle with inactivity. Alongside insulin- and amino acid-resistance [2, 9, 11, 12], this downregulation of translational machinery drives initial losses in muscle mass through dampened myofibrillar protein synthetic responses [2, 12]. As a transducer of the phosphatidylinositol-3-kinase (PI3K)-AKT pathway, mTORC1 is also central to muscle proteostasis via temporal coordination of anabolic and catabolic processes [13].…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned blunted anabolic response to protein/amino acid feeding is known as ‘anabolic resistance’. MPB, on the other hand, either remains unchanged [ 54 , 56 , 57 ] or has been shown to decline [ 55 , 56 ], suggesting that bulk MPB does not appreciably contribute to disuse muscle atrophy in post-pubertal humans, which is also supported by mathematical estimates [ 58 ]. Deficits in fasted/fed MPS, as opposed to increases in MPB, should be considered the driving force of immobilisation-induced atrophy in humans in being sufficient in itself to explain muscle mass lost [ 57 , 59 ].…”
Section: Metabolic Muscle Proteostasis and Links To Human Disuse Atrophymentioning
confidence: 93%
“…MPB, on the other hand, either remains unchanged [54,56,57] or has been shown to decline [55,56], suggesting that bulk MPB does not appreciably contribute to disuse muscle atrophy in post-pubertal humans, which is also supported by mathematical estimates [58]. Deficits in fasted/fed MPS, as opposed to increases in MPB, should be considered the driving force of immobilisation-induced atrophy in humans in being sufficient in itself to explain muscle mass lost [57,59]. This may be caveated in that disease-associated muscle atrophy could be a consequence of decreased MPS and increased MPB due to prevailing systemic factors, e.g., circulating cytokines and cortisol, commonly associated with disease's (e.g.…”
Section: Metabolic Muscle Proteostasis and Links To Human Disuse Atrophymentioning
confidence: 99%
“…Perturbations in muscle lipid handling have been suggested to underpin the development of anabolic and insulin resistance during muscle disuse. We have previously demonstrated that a shift toward positive nonesterified fatty acid (NEFA) balance occurs across the forearm in response to ingestion of a mixed meal after 2 and 7 days of immobilization, which corresponded with insulin ( 10 ) and anabolic ( 5 , 6 , 12 ) resistance. Presumably this positive balance results in lipid accumulation within the muscle during disuse.…”
Section: Introductionmentioning
confidence: 99%